Materials and Wireless Microfluidic Systems for Electronics Capable of Chemical Dissolution on Demand. (23rd December 2014) - Lee, Chi Hwan; Jeong, Jae‐Woong; Liu, Yuhao; Zhang, Yihui; Shi, Yan; Kang, Seung‐Kyun; Kim, Jeonghyun; Kim, Jae Soon; Lee, Na Yeon; Kim, Bong Hoon; Jang, Kyung‐In; Yin, Lan; et al.
Abstract : Electronics that are capable of destroying themselves, on demand and in a harmless way, might provide the ultimate form of data security. This paper presents materials and device architectures for triggered destruction of conventional microelectronic systems by means of microfluidic chemical etching of the constituent materials, including silicon, silicon dioxide, and metals (e.g., aluminum). Demonstrations in an array of home‐built metal‐oxide‐semiconductor field‐effect transistors that exploit ultrathin sheets of monocrystalline silicon and in radio‐frequency identification devices illustrate the utility of the approaches. Abstract : Triggerable transient electronics are presented with the use of wireless microfluidics to enable complete dissolution of conventional microelectronic systems on demand in a controlled, programmable manner. Demonstration examples include triggered destruction of home‐built metal‐oxide‐semiconductor field‐effect transistors and commercial microchips in radio‐frequency identification device.